Semi-interpenetrating polymer networks prepared from castor oil-based waterborne polyurethanes and carboxymethyl chitosan. (15th March 2021) - Zhang, Wenbo; Deng, Henghui; Xia, Lijuan; Shen, Lan; Zhang, Chaoqun; Lu, Qiming; Sun, Shaolong
Highlights: Castor oil-based polyurethane/carboxymethyl chitosan composites were prepared. Effect of carboxymethyl chitosan on the properties of the composites was studied. Hydrogen bonding and interpenetrating networks enhanced the composite properties. The composite dispersion exhibited excellent storage stability and high bio-content. Abstract: A series of vegetable oil-based waterborne polyurethane composites were prepared through construction of novel semi-interpenetrating polymers network using carboxymethyl chitosan (CA) as the secondary polymer phase. The effects of CA contents on storage stability, and particle size distribution of the composite dispersions and thermal stability, mechanical properties and surface wettability of composite films were investigated and discussed. The results showed that the composite dispersions displayed excellent storage stability and the biomass contents of resulting films were high up to 80 %. A significant increase in crosslinking density and glass transition temperature of the composite films were observed as the CA contents increased, which was attributed to the increasing hard segment of films and strong hydrogen bonding interaction between polyurethanes and CA. This work provided a simple method to tailor the performance of environmentally friendly vegetable oil-based waterborne polyurethane, which could find application in the field of coatings, adhesives, ink and so on.